Metodología en movimiento - Avilés Conesa, Ángel David (2025)
This article addresses the methodological dynamics of ethnographic work in the context of social resistance to the granting of mining projects embedded within the extractivist model in the Altiplano-Wirikuta region (Mexico). We relate the design of the research object with the role of the researcher, and both with access to the groups, as dynamic processes of interaction that adjust according to social dynamics that cannot be fixed into static categories. We present this autoethnography as a methodological reflection that seeks to offer tools for the praxis of local resistance, reaffirming the role of anthropology as a discipline with the potential to co-influence and engage with resistance movements seen as drivers of change in the face of extractivism and other global threats.